Towards Inclusive Innovation: Gender and Youth in Sustainable Farming Systems - Mokhema, Seipati; Euler, Michael; Begum, Khadija; Cole, Steven; Huyer, Sophia; Mayanja, Sarah; Mwakanyamale, Devis; Paez-Valencia, Ana Maria; Puskur, Ranjitha (CGIAR System Organization, 2025)
This brief is linked to the Science Program (SP) on Sustainable Farming, which builds on the initiatives: Excellence in Agronomy (EiA), Plant Health (PH) and Mixed Farming Systems (MFS). The Sustainable Farming Program aims at efficient production of more nutritious foods while protecting the environment and also translating this growth into decent and equitable employment opportunities. The SP will co-develop and validate a stream of integrated agronomic, plant health, and farming system solutions. These solutions aim to catalyze adaptation and scaling through a coherent approach that integrates effective data management, prioritization tools, capacity sharing, and partnerships built around contextualized demands. While the program makes explicit reference to women, youth, and marginalized groups as key targets for bundled innovations, there is a need for a more nuanced and inclusive focus to explain how these groups will benefit from the proposed innovations. We therefore identify three GESI focal areas for the Sustainable Farming SP. First, climate change threatens to reverse previous productivity gains in agriculture (IPCC 2022). Women and resource-poor farmers suffer disproportionally from the effects of climate change (Hallegatte 2016). Climate-smart, gender- and socially inclusive approaches such as Climate-Smart Agriculture (CSA) can help to enhance the resilience of all the actors in farming systems (Deering and Wright 2023).